THE REPRESENTATION OF LIBERAL FEMINISM THROUGH CARLY WHITTEN'S CHARACTERIZATION ON THE OTHER WOMAN (2014) - Tambotto, Sharon (Universitas Negeri Surabaya, 2023)
The Other Women’s Charlie Whitten is a dynamic and round character. It could be argued that her characterizations, attitudes, and behavior represent the value of liberal feminism. It depicts some issues regarding gender issues, where women are seen and treated lowly by a man. Moreover, Liberal feminism is a branch of feminism that advocates eliminating gender inequality through having equal rights for both genders. It focuses on women’s ability to show and maintain their equality and maintain their equality through their actions and choices. This film is about Carly as a successful career woman who is cheated by a man named Mark. After she meets with Kate, Mark’s wife, and Amber, Mark’s other mistress, they plan revenge for Mark. Furthermore, the characterization of Carly depicts liberal feminism’s personal autonomy proposed by Emily Baehr (2007). This study will use a qualitative method to reveal the representation of liberal feminism of Carly Whitten. Moreover, the analysis of characterizations and find out that Carly has smart, hard-working, independent, supportive, and determined characteristics. Therefore, those characteristics will be used to analyze the idea of personal autonomy presented by Carly Whitten.